Self-employment in an equilibrium model of the labor market - Bradley, Jake (Springer, 2016)
Self-employed workers account for between 8% and 30% of participants in the labor markets of OECD countries, Blanch ower (2004). This paper develops and estimates a general equilibrium model of the labor market that accounts for this sizable proportion. The model incorporates self-employed workers, some of whom hire paid employees in the market. Employment rates and earnings distributions are determined endogenously and are estimated to match their empirical counterparts. The model is estimated using the British Household Panel Survey (BHPS). The model is able to estimate nonpecuniary amenities associated with employment in di erent labor market states, accounting for both different employment dynamics within state and the misreporting of earnings by self-employed workers. Structural parameter estimates are then used to assess the impact of an increase in the generosity of unemployment benefits on the aggregate employment rate. Findings suggest that modeling the self-employed, some of whom hire paid employees implies that small increases in unemployment benefits leads to an expansion in aggregate employment.